Fungsi Pengawasan DPRD dalam Tata Kelola Penanggulangan Bencana Banjir di Kabupaten Kampar Tahun 2024 - Gilang Ramadhani; Agus Susanto (Institut Pemerintahan Dalam Negeri, 2026)
Flood disaster management is a local government affair that requires legislative oversight to ensure its implementation complies with statutory regulations and responds to community needs. The oversight function of the Regional People’s Representative Council (DPRD) of Kampar Regency in 2024 became crucial given the recurrent nature of flooding and its significant impact on the social and economic lives of the community, particularly in Kampar Kiri District. This study aims to analyze the implementation of the DPRD’s oversight function and to identify factors influencing the optimization of such oversight. This research employs a descriptive qualitative approach, with data collected through interviews and documentation, and analyzed using an interactive analysis model. The findings indicate that the oversight function of the Kampar Regency DPRD over the local government in flood disaster management in 2024 has not been implemented optimally. This suboptimal performance is reflected in the ineffective execution of oversight across the indicators of setting oversight standards, evaluative actions, and corrective actions as proposed in Siagian’s Supervision Theory. In particular, weaknesses are evident in the indicators of evaluative and corrective actions, which are directly related to field supervision, the absorption of public aspirations, and policy recommendations..Factors supporting the optimization of the DPRD’s oversight function include the existence of functional working relationships between the DPRD and local government agencies. Meanwhile, inhibiting factors consist of weak DPRD oversight, which has resulted in delays in the realization of assistance, discrepancies between flood management implementation and the mandates of local regulations, ineffective long-term disaster mitigation, weak formal coordination among institutions in flood management, and the underutilization of DPRD oversight instruments. The novelty of this study lies in its contribution to scholarly discourse by examining the DPRD’s oversight function in disaster management at the regency level through an integrative approach that combines political, institutional, and public policy dimensions. This approach has been rarely addressed in previous studies, which have generally focused on technical aspects of disaster management or policy implementation alone, and thus this research seeks to fill that gap. Furthermore, prior studies have predominantly concentrated on watershed (DAS) policy formulation and general oversight of local policies.